Dual mode microstrip open loop resonator and filter for wireless lan applications - Nik Mustaffa, Nik Khatijah (2013)
Bandpass filters play a significant role in wireless communication systems. Transmitted and received signals have to be filtered at a certain center frequency with a specific bandwidth. The major problem in design microstrip bandpass filter is to get a deeper and wider rejection bandwidth. In this thesis, a dual mode microstrip open loop resonators and filter is design to be operated at 5.7 GHz for wireless local area network (WLAN) using sonnet lite simulation software. Results have been analyzed in terms of reflection coefficient and transmission coefficient. The simulated filter performances are presented. The simulated result shows the performance of bandpass is better for resonator with contact feed compared with non contact feed.